2018
DOI: 10.3390/nu10101562
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cistanche Tubulosa Extracts on Male Reproductive Function in Streptozotocin–Nicotinamide-Induced Diabetic Rats

Abstract: Diabetes is a chronic disorder characterized by hyperglycemia due to decreased levels of insulin or the inefficiency of the tissue to use it effectively. Infertility is known as a major outcome of diabetes and affects the male reproductive system by causing sperm impairment and gonadal dysfunction. Cistanche tubulosa is a parasitic plant which has the capacity to improve memory, immunity, and sexual ability, reduce impotence, and minimize constipation. This study was focused on the investigation of the anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…We further determined the sexual hormones and observed a trend of increase in testosterone after the intervention, instead, no signi cance was found in estradiol. These data were consistent with abundant of previously reported in vivo data, which showed that the cistanche extract increased testosterone level and improved reproductive dysfunction in rats [23][24][25][26]. No report about the effect of cistanche on estradiol for now.…”
Section: Discussionsupporting
confidence: 93%
“…We further determined the sexual hormones and observed a trend of increase in testosterone after the intervention, instead, no signi cance was found in estradiol. These data were consistent with abundant of previously reported in vivo data, which showed that the cistanche extract increased testosterone level and improved reproductive dysfunction in rats [23][24][25][26]. No report about the effect of cistanche on estradiol for now.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, they can lead to and restore spermatogenesis [ 21 ]. The initiation and maintenance of mammalian infertility are connected with G-protein coupled receptor 54 (GPR54) [ 22 ]. The mutation in GPR 54 is characterized by the absence of sexual maturation and low levels of gonadotropin releasing hormones (GnRH).…”
Section: Infertilitymentioning
confidence: 99%
“…ROS contributes to inflammation and it is one of the causes of infertility [ 22 ]. Long-term high oxidative stress and chronic inflammation affect the reproductive system.…”
Section: Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many chronic inflammations are very likely involved in the pathogenesis of insulin resistance and type II diabetes [3]. Oxidative stress (OS) is involved in the pathogenesis of DM partly via reactive oxygen species (ROS) generation in diabetic human and animal models [4]. Several researchers have examined oxidative stress markers in diabetic rats and found increased ROS levels in pancreatic islets [5].…”
Section: Introductionmentioning
confidence: 99%